เงื่อนไขการมีผลเฉลยของ Bitwise XOR Game - ภราดร พรฆัง (จุฬาลงกรณ์มหาวิทยาลัย, 2021)
The Bitwise XOR Game is a mathematical game proposed by Ed Pegg Jr. The game applies the principle of the bitwise XOR operation to a binary numeral system. A player is given a random collection of 9 cards from 63 unique cards, each card is represented by six rectangles which can be in either black or white color. Then the player must pick 3 to 5 cards so that the total number of black rectangles in each of the six positions is even. In this project, we analyze the existence of a solution by examining the number of rectangles "n" in each card, the number of distinct random cards "m" that the player gets, and the numbers of cards from 3 to "k", which can be used as a solution for the game. We found that the conditions n = 6, m = 9, and k = 5 can guarantee the existence of solutions.